Tinjauan Yuridis Perlindungan Hukum Hak Ahli Waris dalam Sita Umum Kepailitan (Studi Kasus Putusan MA No.3471k/Pdt/2023) - Gloria Agatha Hartono; Gunawan Djajaputera (Jurnal Hukum Lex Generalis, 2024)
The protection of heirs' rights to inherited assets that fall under general bankruptcy proceedings has become a significant legal issue in Indonesia. Under the Indonesian legal system, heirs are entitled to receive the inheritance of a decedent. However, this right is often hindered when the inherited assets are included in the bankruptcy estate (boedel pailit) to settle the debts of the deceased. This study employs a normative legal research methodology. Based on the findings, the Bankruptcy Law and the Indonesian Civil Code (KUHPerdata) provide a legal basis for heirs to safeguard their rights, including through the mechanism of beneficium inventarii. Nonetheless, the implementation of this protection faces several challenges, such as limited legal awareness, complex legal procedures, and the lack of consistent jurisprudence. Through an analysis of regulations and Supreme Court decisions, such as Case Number 3471 K/Pdt/2023, this study highlights the need for harmonization between inheritance and bankruptcy laws, as well as the simplification of legal procedures to ensure the protection of heirs' rights without undermining the principle of paritas creditorum. Legal education, the development of consistent jurisprudence, and collaboration among stakeholders are identified as strategic steps to achieve a balance between creditors' interests and heirs' rights.